A comparative study on optic nerve function, retinal nerve fibre layer thickness and vep pre and 3 months post treatment with ethambutol in tuberculosis patients - Penny Tevaraj , Jessica Mani (2017)
Ethambutol is a first line drug for the treatment of tuberculosis. However this drug has caused incidences of irreversible ocular toxicity. This study is to compare the anatomical and visual function using conventional optic nerve function tests, measurement of retinal nerve fibre layer and pattern visual evoked potential changes in patients with tuberculosis treated with a regime containing ethambutol. This is a prospective study involving 72 eyes of 36 patients treated with ethambutol according to the Directly Observed Treatment Short Course (DOTS) strategy in Hospital Universiti Sains Malaysia, Kelantan, Malaysia. The optic nerve function, retinal nerve fibre layer (RNFL) on optical coherence topography (OCT) and pattern visual evoked potential (PVEP) were assessed. The examination was performed before the start of therapy and three months after. Visual field analysis of mean deviation (md) showed significant statistical change (p=0.010). There were also significant changes on OCT and PVEP. Comparison of RNFL thickness showed an increased thickness in all quadrants (p<0.05) and a delayed P100 peak latency and decreased amplitude on PVEP assessment (p<0.001). There was no change in visual acuity, colour vision, light brightness, red saturation and fundus findings pre and post ethambutol. The use of OCT to detect RNFL thickness and PVEP to assess P100 latency and amplitude can assist in the detection of subclinical anatomical and visual function changes prior to conventional optic nerve function tests. These changes may represent early ethambutol related optic neuropathy, making OCT and PVEP important tools in monitoring tuberculosis patients.